MENINGKATKAN KEPATUHAN PAJAK WPOP MELALUI ASISTENSI PELAPORAN SPT E-FILING - Selvia; Lukman, Hendro (Jurnal Serina Abdimas, 2024)
The Annual Tax Return is one of the taxpayers' obligations to fulfill their tax obligations in the self-assessment system. Annual Tax Returns are reported using the e-filing system no later than March 31 of the following tax year. Awareness of reporting tax obligations is an indication of tax compliance. Understanding the obligations of Individual Taxpayers (WPOP), as well as the problems and difficulties that arise in the process of reporting Annual Tax Returns via e-filing. Many WPOP do not understand or have difficulty using the e-filing system, and the available tax personnel are not commensurate with the growth in the number of WPOP to provide assistance in filling out reports using the e-filing system. Therefore, the Directorate General of Taxes formed Tax Volunteers from students to help tax officers assist WPOP in filling out Tax Returns by e-filing. Apart from that, helping and encouraging increased tax compliance through socializing the obligation to report annual taxes. Tax volunteers helping WPOP at the Cengkareng Tax Service Office is one of the Community Service activities that has been carried out during March 2024. ABSTRAK Surat Pemberitahuan Tahunan merupakan salah satu kewajiban wajib pajak untuk memenuhi kewajiban perpajakannya dalam sistem selfassement. Pelaporan Surat Pemberitahuan Tahunan dilaporan dengan sistem e-filing paling lambat pada tanggal 31 Maret tahun pajak berikutanya. Kesadaran melaporkan kewajiban perpajakan merupakan indikasi pada kepatuhan pajak. Pemahaman kewajiban Wajib Pajak Orang Pribadi (WPOP), serta permasalahan dan kesulitan yang timbul dalam proses pelaporan Surat Pemberitahuan Tahunan melalui e-filing. Banyak WPOP yang belum memahami atau mengalami kesulitan dalam menggunakan sistem e-filing, dan tenaga perpajakan yang tersedia tidak sebanding dengan pertumbuhan jumlah WPOP untuk melakukan asistensi pengisian pelaporan dengan sistem e-filing. Oleh karena itu, Direktorat Jenderal Pajak membentuk Relawan Pajak dari mahasiswa untuk membantu petugas pajak mengasistensikan WPOP mengisi Tax Return dengan e-filing. Selain itu, membantu dan mendorong peningkatan kepatuhan pajak melalui sosialisasi kewajiban melaporkan pajak tahunan. Relawan pajak membantu WPOP di Kantor Pelayanan Pajak Cengkareng merupaakan salah satu kegiatan Pengabdian Kepada Masyarakat yang telah dilaksanakan selama bulan Maret 2024.